Agile Gamification Risk Management Process: A Comprehensive Process for Identifying and Assessing Gamification Risks - Fayrouz M. Elsalmy; Nada H. Sherief; Walid M. Abdel Moez; Hany H. Ammar (Computers)
Gamification has become a motivational technique for enhancing engagement and productivity, extending into agile software development. However, integrating gamification into agile frameworks such as the Scrum framework has led to the emergence of gamification risks, which may have adverse impacts on agile roles and tasks. These risks include an increase in the number of unassigned tasks affecting sprint velocity, novelty-seeking and quick boredom, clustering group, and intimidation, thus showing the need for a structured approach toward their management, their impacts on team dynamics and project outcomes. This study proposes the Agile Gamification Risk Management (AGRM) process, focused on identifying, assessing, and mitigating gamification risks in agile software enterprises. AGRM introduces artifacts such as the Gamification Risk Reporting Form, Personalized Risk Profiles, Task Impact Matrix, and Gamification Risk Register, enabling real-time proactive risk management. By leveraging a gamification risk taxonomy, AGRM categorizes and prioritizes risks, aligning mitigation efforts effectively. This paper details a two-phased empirical study to evaluate our proposed AGRM process. The proposed process identified 17 and mitigated 9 gamification risks for two agile teams in two software development enterprises. Unlike ad hoc practices, AGRM provides a structured approach, empowering teams to manage risks during sprint events. By incorporating artifacts like the Gamification Risk Register (GRR) and Personalized Risk Profiles (PRPs), teams can assess risks in context, enhancing productivity, collaboration, and project outcomes. The results demonstrate AGRM’s ability to boost team morale and confidence in addressing gamification risks effectively.